Emotional Processing, P50 Sensory Gating, and Social Functioning in Bipolar Disorder. (April 2015) - Vuillier, Laura; Hermens, Daniel F.; Chitty, Kate; Wang, Chenyu; Kaur, Manreena; Ward, Philip B.; Degabriele, Rachael; Hickie, Ian B.; Lagopoulos, Jim
Emotional processing has been reported to effect sensory gating as measured by the event-related potential known as P50. Because both P50 and emotional processing are dysfunctional in bipolar disorder (BD), we sought to investigate the impact that concurrent emotional processing has on sensory gating in this psychiatric population. P50 was recorded using a paired-click paradigm. Peak-to-peak amplitudes for stimulus 1 (S1) and stimulus 2 (S2) were acquired during the presentation of disgust and neutral faces to young adults with BD (n = 19) and controls (n = 20). Social functioning and quality-of-life self-reported measures were also obtained. The BD group had significantly larger P50 amplitudes elicited by the S2-disgust response compared with controls, but no significant difference in overall P50 sensory gating was found between the groups. There were also no differences between groups in S1-disgust or in either of the neutral P50 amplitudes. The BD group showed significant associations between sensory gating to disgust and measures of social functioning. Importantly, BD showed impaired filtering of auditory information when paired with an emotionally salient image. Thus, it appears that patients with the greatest impairment in sensory gating also have the most difficulty engaging in social situations.